Mapping Teacher Competencies Associated with Teacher Certification: A Systematic Review - Inu Kertapati (Journal of Educational Sciences, 2026)
This study aims to systematically map teacher competencies related to teacher certification and address fragmented understanding of how certification aligns with contemporary competency requirements. Using the PRISMA approach, 723 articles were identified from the Scopus database, and 16 empirical studies selected following a rigorous screening process. The findings indicate that teacher certification is primarily associated with professional and pedagogical competencies, reflecting its primary function in ensuring the quality of basic instruction. Pedagogical Content Knowledge (PCK) emerges as a key mechanism linking certification to teaching effectiveness. However, competencies that are increasingly critical in modern education such as social, motivational, and digital competencies remain underrepresented in the literature. This imbalance highlights a mismatch between certification systems and the evolving demands of 21st-century education. The findings indicate that the effectiveness of certification varies across educational contexts and is strongly influenced by policy design, institutional capacity, and the integration of continuous professional development. This study contributes by presenting a structured competency mapping and identifying a conceptual shift from certification as a compliance-based mechanism toward a competency development oriented system. The results provide practical implications for policymakers and educational institutions to design certification systems that are more adaptive, integrated, and aligned with future competency demands.